DIFFERENCES IN POSSIBLE REACTIONS OF THE EU FARMERS FROM SELECTED EUROPEAN REGIONS TO CAP CHANGE - Edward Majewski; Meri Raggi; Piotr Sulewski; Davide Viaggi (Acta Scientiarum Polonorum. Oeconomia, 2011)
The aim of this paper is to analyze the likely reaction of farmers to different Common Agricultural Policy scenarios. Farmers’ declarations regarding continuation of farming and farm management decision were the key issues examined in the study. The study was conducted in selected regions of several EU countries within the CAP-IRE project. Data has been collected through a farm survey with the use of an interview questionnaire. There were two hypothetical policy scenarios considered: Baseline, that assumes the continuation of the present EU agricultural policy, and Liberalization, assuming that all forms of public support for the farming sector are withdrawn. The McNerman test was the main tool used for statistical analysis. Research revealed significant differences in reaction of farmers from different regions of the EU countries represented in the study. However, on average, more farmers declared they would rather stopped farming under the no-CAP Liberal scenario and expressed greater interest in off-farm activities than in the Baseline scenario.